Development of an e-module for sensors and transducers using Kvisoft Flipbook to enhance 4Cs skills in vocational education students - Andre, Joni; Ramadhani, Witri; Syahril, Syahril; Purwanto, Wawan; Irfan, Dedy; Basri, Irma Yulia (Universitas Negeri Padang, 2024)
This research aims to develop sensor and transducer e-modules based on 4Cs skills using the Kvisoft Flipbook application to improve the quality of learning in automotive engineering. The main focus of the research is to assess the validity, practicality, and student response to the e-module design developed. The research method used is Research and Development (R&D) with the ADDIE model. Data collection techniques included validation questionnaires, user practicality questionnaires, and student response questionnaires to the e-modules. The e-module was rated highly valid by 89% of e-module experts and 88% of material experts and highly practical according to the assessment of lecturers (89.09%) and students (81.81%). The evaluation showed that students who used the e-module achieved a higher average score than the control group, signalling the effectiveness of the e-module in improving critical thinking skills, communication, collaboration, creativity (4Cs), and material understanding. These findings emphasize the importance of technology integration in vocational education to prepare students for the challenges of the Industrial Revolution 4.0 and encourage innovation in teaching methodologies.